2017
DOI: 10.3892/mmr.2017.6557
|View full text |Cite
|
Sign up to set email alerts
|

C-terminus of OX2R significantly affects downstream signaling pathways

Abstract: The human orexin 2 receptor (OX2R) is a G-protein-coupled receptor (GPCR) that has been implicated in a number of diverse physiological functions. Recent studies have identified a number of functions of the C-termini of GPCRs. However, the importance of the OX2R C-terminus in regulating signaling and surface expression remains unclear. In the present study, the function of the OX2R C-terminus was investigated using three C-terminal mutants, which were truncated at residues 368, 384 and 414, respectively, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recent studies indicated the interaction of cAMP and calcium as the potential therapeutic targets for the treatment of neurological diseases [37]. As reported, OX2R activation regulated cellular cAMP and calcium levels [18,19]. However, 5-HT1AR activation reduced the cellular cAMP levels, while having no effect on calcium influx [10].…”
Section: -Ht1ar-ox2r Heterodimer Changed the Cellular Camp And Calcimentioning
confidence: 87%
See 2 more Smart Citations
“…Recent studies indicated the interaction of cAMP and calcium as the potential therapeutic targets for the treatment of neurological diseases [37]. As reported, OX2R activation regulated cellular cAMP and calcium levels [18,19]. However, 5-HT1AR activation reduced the cellular cAMP levels, while having no effect on calcium influx [10].…”
Section: -Ht1ar-ox2r Heterodimer Changed the Cellular Camp And Calcimentioning
confidence: 87%
“…As mentioned above, 5-HT1AR mainly binds to the Gi protein, leading to the decrease of adenylate cyclase (AC) activation, and further leads to the downregulation of levels of p-CREB and cellular cAMP after ligand stimulation [15]. And OX2R mainly binds to the Gs protein and Gq protein resulting in the activation of adenylate cyclase (AC), and further leads to the upregulation of the expression levels of p-CREB, p-ERK, cellular cAMP and calcium levels after ligand stimulation [18][19][20]. In the study, we found activation of 5-HT1AR-OX2R heterodimers increased the levels of cAMP and calcium, also led to the downregulation of p-ERK and p-CREB ( Figure 6 and Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HEK293 cells stably expressing APJ were plated at 10 4 cells per well in 96-well black microplates pretreated with a 0.1 mg/ml solution of poly- d -lysine for 24 h. Calcium fluorescence signals in cells were measured using the Fluo-4 NW calcium assay kit (Thermo Fisher Scientific) according to the manufacturer’s instructions ( Chen et al, 2014 ; Wang et al, 2017 ). Before detection, cells were washed twice with assay buffer (1 × HBSS, 20 mM HEPES).…”
Section: Methodsmentioning
confidence: 99%